Conceptual Vectors, A Complementary Tool To Lexical Networks. - Schwab, Didier; Lim, Lian Tze; Lafourcade, Mathieu (2007)
There is currently much research in natural language processing focusing on lexical networks. Most of them, in particular the most famous, word-Net, lack syntagmatic information and especially thematic information (“Tennis Problem"). This article describes conceptual vectors that allows the representation of ideas in any textual segment and offers a continuous vision of related thematics, based on the distances between these thematics. We show the characteristics of conceptual vectors and explain how they complement lexico-semantic networks. we illustrate this purpose by adding conceptual vectors to wordNet by emergence,